2007
DOI: 10.1017/s0003055407070293
|View full text |Cite
|
Sign up to set email alerts
|

İSí Se Puede! Latino Candidates and the Mobilization of Latino Voters

Abstract: T raditional studies of political participation assume an electoral environment in which voters decide between two White candidates, and find Latino citizens less politically engaged. Given the growth in the number of Latino candidates for office over the past 20 years, this article tests whether ethnicity impacts Latino voting behavior. I argue that the presence of a Latino candidate mobilizes the Latino electorate, resulting in elevated voter turnout and strong support for the co-ethnic candidates. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
204
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 273 publications
(216 citation statements)
references
References 37 publications
7
204
2
3
Order By: Relevance
“…Previous studies of Asian and Latino candidates have focused on the effect of minority candidacies on minority voters. Masuoka (2006) and Baretto (2007) have found increased participation among Asians and Latinos when they are voting for co-ethnic candidates. Many of these studies are motivated by the fact that, especially among blacks and Latinos, most minority candidates have run in majority-minority districts.…”
Section: Which Races Matter?mentioning
confidence: 99%
“…Previous studies of Asian and Latino candidates have focused on the effect of minority candidacies on minority voters. Masuoka (2006) and Baretto (2007) have found increased participation among Asians and Latinos when they are voting for co-ethnic candidates. Many of these studies are motivated by the fact that, especially among blacks and Latinos, most minority candidates have run in majority-minority districts.…”
Section: Which Races Matter?mentioning
confidence: 99%
“…It assumes that migrants hold strong ethnic identities, and emphasizes the relevance of this identity for their political behavior (e.g. Barreto, 2007). Ethnicity theory relates to the fact that ethnicity is often a good predictor for variance in the political behavior of migrants, and migrants' political mobilization is often framed along ethnic lines.…”
Section: Political Opportunity Structures and The Political Behavior mentioning
confidence: 99%
“…Barreto (2007) (2006) found that Spanish language campaign commercials had a positive and significant impact on Latino turnout, however English commercials had no effect at all. With regard to vote choice in 2000, Nuño (2007) 187 and using strong anti-immigrant rhetoric the result was Latinos flocking to the Democratic Party (Barreto and Woods 2007).…”
Section: Latino Ethnic Politicsmentioning
confidence: 99%